Den neoliberale guvernementalitet, biopolitik og teologi - Interview med Thomas Biebricher - Eggers, Nicolai von (Slagmark - Tidsskrift for idéhistorie, 2018)
In this interview, professor Thomas Biebricher discusses the meaning of Michel Foucault’s notion of ‘governmentality’ by investigating different aspects of ‘neoliberalism’, here understood as a tradition of thought going back to the Mont Pelerin Society. Biebricher first discusses the initial reception of Foucault in Germany and then goes on to talk about some of the initial features of neoliberalism including its biopolitics, its governmentality, and its theological elements. During this discussion, Biebricher also touches upon methodological questions in engaging with Foucault and upon how this relates to political theory and approaches focusing more on institutionalism.